1985
DOI: 10.1177/036354658501300302
|View full text |Cite
|
Sign up to set email alerts
|

Shoulder strength following acromioclavicular injury

Abstract: The acromioclavicular (AC) joint enjoys the dubious distinction of being one of the few joints in the body whose total dislocation is routinely treated by simply leaving the joint dislocated. Adherents of both conservative and operative treatment have presented reasons for their viewpoints. Residual shoulder weakness has been offered as a sequela of untreated acromioclavicular injury and a reason for repairing the joint. An objective evaluation of shoulder strength would be valuable in determining the optimum … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
30
0
2

Year Published

1992
1992
2018
2018

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 84 publications
(32 citation statements)
references
References 5 publications
0
30
0
2
Order By: Relevance
“…26,92 Functional deficits are minimal, with the objective evaluation of shoulder strength reported to be similar to that of the contralateral shoulder at midterm follow-up. 78,84,87 However, there has been a reported 17% loss of bench press strength. 78 Complaints of persistent AC joint tenderness, instability, shoulder stiffness, and cosmetic deformity may require subsequent surgical intervention.…”
Section: Treatment Type I and Type Ii Injuriesmentioning
confidence: 99%
See 1 more Smart Citation
“…26,92 Functional deficits are minimal, with the objective evaluation of shoulder strength reported to be similar to that of the contralateral shoulder at midterm follow-up. 78,84,87 However, there has been a reported 17% loss of bench press strength. 78 Complaints of persistent AC joint tenderness, instability, shoulder stiffness, and cosmetic deformity may require subsequent surgical intervention.…”
Section: Treatment Type I and Type Ii Injuriesmentioning
confidence: 99%
“…78 Complaints of persistent AC joint tenderness, instability, shoulder stiffness, and cosmetic deformity may require subsequent surgical intervention. 87,92 Studies comparing the results of nonoperative and surgical treatment of type III AC separations have shown that surgical intervention does not have a substantial benefit. 3,47,54,68,69,82 In a randomized controlled trial with 4 years of follow-up, Bannister et al 3 compared nonoperative and operative management (with a CC screw) for 42 patients with a type III AC separation and 12 with type V. The patients with type III injuries who were treated nonoperatively obtained full shoulder motion more quickly, returned to work or sport earlier, and had fewer unsatisfactory results than those treated surgically.…”
Section: Treatment Type I and Type Ii Injuriesmentioning
confidence: 99%
“…This is documented in Table 1. Several studies could not document significant strength differences in patients with complete AC dislocations who were treated conservatively [14][15][16][17] (Sellers et al 1988, personal communication). More recently, Zarzycki et al [18] treated 14 athletes with 2-week immobilization and intensive rehabilitation.…”
Section: Resultsmentioning
confidence: 99%
“…Their surgical technique was a transarticular K-wire stabilization of the reduced clavicle. Walsh et al [20] showed that patients treated conservatively after type III AC dislocation had no significant strength deficit tested with an isokinetic dynamometer in comparison to the uninjured shoulder. Nevertheless these patients complained of the most pain and stiffness in their subjective evaluation despite their strong shoulders.…”
Section: Discussionmentioning
confidence: 99%